Human rights : the search for universality. - Morrison, Elizabeth King (My University, 2012)
Human rights in large part have become a topic of seemingly global appeal. They have become a part of the fabric of the global conversation. Especially within the context of the last sixty years, human rights have become an actionable, practical, and in some cases legally binding set of rights. Current human rights hinge on the idea that all humans no matter where or under what circumstances they were born possess certain rights simply because they were born human. This thesis will discuss the universality of human rights in both theory and in practice. To be more specific, human rights will be discussed by exploring the philosophic foundations of human rights. The language that was used in the structuring and development of the human rights was derived from rights instruments which originated during the Enlightenment Period. However, the underlying philosophy is only representational of a percentage of the people and cultures of the world. Because the underlying philosophy is not cross-cultural, moral and cultural relativism bars human rights from being universal. However, the contention of this thesis is to show that despite the limits of universality in terms of relativism and incoherent philosophic underpinnings, human rights are still a force to be reckoned with as a part of a social construction. A human right may not be an inalienable, inherent right that belongs to a person because he or she is human, but it does have some legitimacy on the grounds that social norms have been constructed over time.--Abstract.
Keywords: Human rights; Human rights